Plant-based dietary patterns, micronutrient status and breast cancer outcomes: a joint analysis of UK Biobank and Chinese longitudinal healthy longevity survey - Xu, Weizhe; Gu, Wen; Huang, Yanqiu; Li, Shuli; Liu, Honglin; Zhu, Xun (Frontiers in Nutrition, 2026)
BackgroundPlant-based diets may lower breast cancer risk, but their impact on breast cancer-related mortality is unclear. We explored associations of plant-based dietary patterns (Healthful Plant-Based Diet Index [HPDI/PDI]) and micronutrient intake with breast cancer incidence and all-cause mortality in patients.MethodsUsing data of UK Biobank (UKB; 67,045 cancer-free participants; 3,397 breast cancer patients) and Chinese Longitudinal Healthy Longevity Survey (CLHLS), we analyzed dietary scores and micronutrient intake via multivariate Cox regression, restricted cubic splines, and predictive models (concordance index, Random Forest, and time-dependent ROC).ResultsAmong 67,045 breast cancer-free participants, the highest HPDI tertile was associated with 11% lower breast cancer risk (HR = 0.89, 95%CI: 0.82–0.98) vs. lowest tertile (4% reduction per SD increase, HR = 0.96, 95%CI: 0.93–1.00). Among 3,397 breast cancer patients, the highest HPDI tertile showed 28% lower mortality (HR = 0.72, 95%CI: 0.55–0.95) vs. lowest (11% reduction per SD, HR = 0.89, 95%CI: 0.79–1.00). Individuals with high PDI scores exhibited a 39% lower risk of cancer compared to those with low scores in CLHLS (HR = 0.61, 95%CI: 0.41–0.92). Higher intakes of vitamins B2 and C, calcium, and magnesium were inversely associated with risk and mortality, while each SD increase in sodium raised mortality risk by 15% (HR = 1.15, 95%CI: 1.01–1.32). Predictive models showed optimal 5-year performance overall; micronutrients alone best predicted breast cancer risk across timepoints, while HPDI peaked for 5-year mortality prediction (AUC = 0.625). The combined model achieved superior 10-year prognosis.ConclusionsHigh adherence to a healthful plant-based diet, together with sufficient intake of key micronutrients and reduced sodium consumption, may contribute to breast cancer prevention and improved survival outcomes.